2019
DOI: 10.12659/msm.915963
|View full text |Cite
|
Sign up to set email alerts
|

Role of CircRNAs_100395 in Proliferation and Metastases of Liver Cancer

Abstract: Background Circular RNAs (circRNAs) are a kind of noncoding RNA with high cancer-specific expression, and great potential in regulating tumorigenesis. Among these, circRNA_100395 (circ_100395) has been reported to be downregulated in lung cancer, and participates in the process of tumor cell proliferation and metastasis. However, its expression and function in liver cancer remain unknown. Material/Methods Quantitative real-time polymerase chain reaction (RT-qPCR) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Emerging studies have indicated that cell growth and metastasis are affected by EMT. For example, Shao et al 25 found that NLRP3 promoted colorectal cancer cell proliferation and metastasis by regulating EMT, while Chen et al 14 showed that circRNA_100395 suppressed liver cancer cell proliferation and metastasis by regulating EMT. Collectively, these studies suggest that the mechanism underlying the antiproliferation and anti-metastatic effects of Accumulating studies have also indicated that circRNAs can interfere with the expression of miRNAs by functioning as miRNA sponges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging studies have indicated that cell growth and metastasis are affected by EMT. For example, Shao et al 25 found that NLRP3 promoted colorectal cancer cell proliferation and metastasis by regulating EMT, while Chen et al 14 showed that circRNA_100395 suppressed liver cancer cell proliferation and metastasis by regulating EMT. Collectively, these studies suggest that the mechanism underlying the antiproliferation and anti-metastatic effects of Accumulating studies have also indicated that circRNAs can interfere with the expression of miRNAs by functioning as miRNA sponges.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA_100395 is located at chr1: 173726114–17374498. 13 Emerging evidence has shown that circRNA_100395 is downregulated in tumors, and its expression pattern was strongly associated with lymph node metastasis, tumor size, and overall survival in patients with lung, 13 liver, 14 and ovarian cancers. 15 However, the relationship between circRNA_100395 and prostate cancer is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…circ_RNAs affect human disease, such as changes in the level of ciRS-7/CDR1as (the miR-7 circ_RNA sponge), and alter the levels of miR-7 target genes (both endogenous and reporter) ( 12 , 14 , 17 ). circ_RNAs also play a pivotal role in the pathogenesis and development of a diversity of cancers, such as liver ( 18 , 19 ), colon ( 20 , 21 ), gastric ( 22 , 23 ), lung ( 24 , 25 ), kidney cancer ( 26 , 27 ) and endometrial cancer ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some researches had shown that circRNAs modulated alternative splicing and gene expression level through sponging microRNAs (miRNAs) [ 11 , 12 ]. At the same time, disorders of circRNAs took part in carcinogenesis and cancer development of CRC [ 13 , 14 ], liver cancer [ 15 ], and gastric cancer [ 16 – 19 ]. These findings indicated that circRNAs, as a new kind of endogenous noncoding RNA, have been a new hotspot in the cancer research and probably would exhibit important functions in the development of tumor.…”
Section: Introductionmentioning
confidence: 99%